Commognitive terhadap Proses Berpikir Mahasiswa dalam Menyelesaikan Masalah Program Linear: Studi Kasus pada Mahasiswa S1 Pendidikan Matematika - Yandi Raharjo, Eko (Jurnal Edumatic: Jurnal Pendidikan Matematika, 2025)
Commognitive theory views mathematical thinking as a form of communication that reflects an individual’s conceptial structure in understanding mathematics. This study is motivated by the finding that students often have difficulty in constructing mathematical models and interpreting solutions in the context of linear programs. This study aims to describe the thought process of undergraduater mahtematics education students in solving linear program progrlems based on commognitive theory. With a qualitative case study approach, two students were selected through purposive sampling technique and analyzed using problem solving questions, think aloud, and clinical interviews. The data were analyzed based on four commognitive components: word use, visual mediator, narratives, and routines. The results showed that subject M1 was able to construct a logical and coherent mahtematical narrative, although there were still deficiencies in the formula explicitness. In contrast, Subject M2 showed ritualistic mathematical communication, accompanied by logical leaps and incomplete procedures.